REGION PEOPLE SUBSIDIARITY AND CULTURAL SUSTAINABILITY DIRECTIONS (International Conference on Economics, Finance, Banking and Management, 2025)
This article discusses the principle of subsidiarity in the development of family entrepreneurship, as this principle gives family business entities the right to independently organize and conduct their activities. Family entrepreneurship, as a form of small-scale economic activity, is characterized by local decision-making on the basis of subsidiarity, efficient use of resources, and assessment of development opportunities in accordance with their own needs without external intervention.